ERRORS ANALYSIS OF THE USE OF COHESIVE DEVICE BY THE STUDENTS OF THE 6th SEMESTER OF STBA PIA MEDAN - Simanjuntak, Winaria Peggy Lovianna (Bahasa Indonesia Prima, 2021)
Abstract-This research aims to analyze the error of the use of cohesive device by the students of 6th semester of STBA PIA Medan in the terms of (1) the types of errors in the use of cohesive device and (2 ) the causes of errors in using cohesive device made by the students of 6th semester of STBA PIA Medan This research uses Descriptive qualitative research method. The analysis of the students’ errors in using cohesive device were conducted based on the category of errors, namely : addition, ommision, substitution and ordering. The data was a text of opinion ( argumentative) which were written by the students. The Results of the analysis are taken as follows : There were four types of error made by the students, namely : Errors of addition (21,4%), errors of omission (26,8%), errors of substitution (36,9%) and errors of ordering 14,7 %). After the errors were viewed from the four types of the students’errors, the dominant type of errors which is made of the students is substitution ( 36,9%). The causes of errors were interlingual, intralingual and disability to observe the restrictions of existing language structures. Keyword: Error analysis, cohesive device, opinion text.